Intermittent protein restriction before but not after the onset of diabetic kidney disease attenuates disease progression in mice - Peng, Xiaoyue; Liu, Min; Wu, Yijie; Fan, Wenying; Hou, Yi; Kong, Yan; Liu, Yajin; Zhang, Xuejiao; Shan, Chunyan; Sun, Haipeng; Yang, Yanhui (Frontiers in Nutrition, 2024)
Background High dietary protein intake exacerbates proteinuria in individuals with diabetic kidney disease (DKD). However, studies on the impacts of low protein diet (LPD) on DKD have yielded conflicting results. Furthermore, patient compliance to continuous protein restriction is challenging. Objective The current study aims to investigate the effects of intermittent protein restriction (IPR) on disease progression of DKD. Methods Diabetic KK-Ay mice were used in this study. For the IPR treatment, three consecutive days of LPD were followed by four consecutive days of normal protein diet (NPD) within each week. For early intervention, mice received IPR before DKD onset. For late intervention, mice received IPR after DKD onset. In both experiments, age-matched mice fed continuous NPD served as the control group. Kidney morphology, structure and function of mice in different groups were examined. Results Intermittent protein restriction before DKD onset ameliorated pathological changes in kidney, including nephromegaly, glomerular hyperfiltration, tubular injuries and proteinuria, without improving glycemic control. Meanwhile, IPR initiated after DKD onset showed no renoprotective effects despite improved glucose homeostasis. Conclusion Intermittent protein restriction before rather than after DKD onset protects kidneys, and the impacts of IPR on the kidneys are independent of glycemic control. IPR shows promise as an effective strategy for managing DKD and improving patient compliance.